China coup : the great leap to freedom - Garside, Roger (University of California Press, 2021)
"Before the next National Congress of the Communist Party of China, due in November 2022, President Xi Jinping will be removed from office by a coup d'état mounted by rivals in the top leadership who will end the tyranny of the one-party dictatorship and launch a transition to democracy and the rule of law. The main body of this book, Part 2, explains why it will happen. Parts 1 and 3 tell how it may happen"--